The Determinant Factors of Preeclampsia Incidence in Pregnant Women at Haji Hospital Makassar in 2024 - Usman, Nurul Azizah; Mappaware, Nasrudin Andi; Gunawan, Witono (Journal La Medihealtico, 2025)
Hypertensive disorders during pregnancy, particularly preeclampsia, are a leading cause of maternal and perinatal mortality worldwide. Preeclampsia can progress into severe complications such as eclampsia and HELLP syndrome. Factors such as age, pregnancy history, and body mass index (BMI) are known to play a role in the occurrence of this condition. This study was conducted at RSUD Haji Makassar to identify determinant factors influencing the occurrence of preeclampsia in pregnant women. This study used a descriptive-analytical approach with a retrospective design, where secondary data were obtained from medical records of patients diagnosed with preeclampsia during a specific period (year 2024). Analysis was performed on factors influencing the incidence of preeclampsia in pregnant women at RSUD Haji Makassar. Age, parity, BMI, and height significantly influenced the occurrence of preeclampsia. Older age and higher parity increased the risk of preeclampsia. Higher BMI and shorter height were also associated with higher blood pressure, which worsened the condition. However, gravida and weight did not show significant effects. Age, parity, BMI, and height are significant determinants of preeclampsia. Management and prevention of preeclampsia should consider these factors to improve maternal and fetal safety during pregnancy.